TRADITIONAL ASPECTS IN SUSTAINABLE FASHION PRACTICE (Journal of Creative Industry and Sustainable Culture, 2023)
Sustainable issues have been forced for the fashion industry stakeholders to develop sustainable practices. Many strategies were attempted to overcome these issues, and one of the established sustainability strategies is to employ a traditional approach in their practices. As an archipelago country, Indonesia has a diverse traditional cultural heritage, which allows local fashion brand owners to use them in their practice. The importance of the traditional approach is learning and considering each community's existing culture. One of the established fashion practices in Indonesia that has employed traditional aspects as their primary approach is Threads of Life. This research aims to analyze the traditional aspect of Thread of Life practice and observe how the aspect of tradition plays a significant role in achieving sustainable fashion. This study uses a qualitative descriptive method with a single embedded case study by taking Threads of Life as the case study, focusing on traditional aspects of achieving sustainable practices. The analysis process focused on three units of analysis: production process, business model, and design. The research outcome is a model that explains the traditional aspect of the Threads of Life. The model shows that designing sustainable products focusing on traditional aspects should contain five aspects (environmental, social, economic, traditional aesthetics, and indigenous) with various strategies.